Gene Muatatuion Changes in Adenocarcinoma Lung Cancer Patient With Left Pyopneumothorax - Nurandhini, Marsha; Suryanti Dwi Pratiwi; Yani Jane R. Sugiri; Dini Rachma Erawati; Hendy Setyo Yudhanto (Universitaas Brawijaya, 2025)
Introduction: Adenocarcinoma is the most common subtype of lung cancer, around 40% of lung cancer cases worldwide. It’s specific to epidermal growth factor receptor (EGFR) mutation. Lung cancer can be risk factor and increases the mortality rate of pyopneumothorax (12.8% higher in cancer patients). Case Illustration: A 69 year old woman, non smoker, who is diagnosed with lung adenocarcinoma (Exon 18 and 21 mutation) in May 2021 and came to emergency room with complaints of worsening shortness of breath. Cloudy-yellow pleural fluid was drained during thoracocentesis procedure. Imaging study using thorax CT scan showed a left lung mass obliterating bronchial segments 1/2, 3 and left hydropneumothorax. The patient was later diagnosed with pyopneumothorax and thorax drain procedure was performed. Antibiotic therapy was based on culture result. Through a following ctDNA (circulating tumor DNA) test, the mutations change to Exons 19 and 20 T790M. Discussion: Pyopneumothorax in this patient can occur due to disorder in the integrity of the host defense mechanisms, which then develops infection in the pleural cavity. The T790M mutation is found in 50-60% cases that are resistant to tyrosin kinase inhibitors (TKI). Third-generation TKI is main option for this condition, however, platinum-based chemotherapy can be considered, as in the case above, where third-generation chemotherapy cannot be given due to limitation of insurance coverage. Conclusion: Lung cancer can be associated with occurance of pyopneumothorax. Genetic mutation changes can occur due to resistance mechanisms. Giving platinum-based chemotherapy can be considered in such cases. Keywords: lung adenocarcinoma, genetic mutation, pyopneumothorax